Trichothecenes from the fungus Acremonium crotocinigenum BCC 20012. (December 2016) - Bunyapaiboonsri, Taridaporn; Yoiprommarat, Seangaroon; Lapanun, Sanisa; Balram, Upin; Chanthaket, Rungtiwa; Klaysuban, Anupong; Suetrong, Satinee
Graphical abstract: Highlights: Three new trichothecenes were isolated from Acremonium crotocinigenum BCC 20012. A new chloroderivative possesses tetrahydropyran instead of 12, 13-epoxy ring. The known trichothecin showed antimalarial activity with IC50  = 0.05 μg/mL. Abstract: Two new trichothecenes (1 and2 ) and a new chloroderivative of a trichothecene analogue (3 ) together with four known trichothecenes, crotocin, trichothecin, 8-deoxytrichothecinol B, and a trichothecene analogue, were isolated from the fungus Acremonium crotocinigenum BCC 20012. The structures of these compounds were elucidated by extensive spectroscopic analysis. Among the tested metabolites, trichothecin itself showed strongest antimalarial activity against Plasmodium falciparum K1, and cytotoxic activity against Vero cell lines with IC50 values of 0.05 and 0.13 μg/mL, respectively.